Biodigester attribute tradeoffs among farmers in Kiambu and Machakos Counties, Kenya - Mailu, Stephen; Irungu, Patrick; Kiriamiti, Henry; Rewe, Thomas; Kinusu, Kevin (SSRN, 2022)
The diffusion of biodigester technology can contribute support towards the achievement of the global goals brokered under the auspices of the United Nations. They have been promoted among farmers but low adoption remains a challenge. Meanwhile, since biodigesters come in different technical designs, they have corresponding performance attributes. While theory suggests that potential adopters trade off these attributes, information about these tradeoffs is currently unavailable. Developing an understanding of how a potential adopter trades-off these attributes can reveal important information which technology developers and information providers should consider when promoting the technology. After presenting the underlying random utility framework, a choice experiment (CE) was designed. Six attributes in the CE describing the technology included its installation cost, reliability, durability, maintenance cost, movability, and ease of defect identification. Based on the modified Fedorov algorithm, an efficient design was constructed. This resulted in 64 hypothetical alternatives in total, split into 2 blocks and presented as a series of 8 choice tasks per respondent. Each choice situation had an opt-out alternative and three generic choice profiles. A random sample of 455 coffee farmers from Kiambu and Machakos provided data used in the analysis. Estimation was implemented through application of a mixed logit model. Results suggested that respondents were willing to forego a cost of 8,400KES for easy defect identification. This suggests the desirability of coupling individual biodigester units with IoT-based sensor instrumentation. This can enhance the continued functioning of biodigesters and stimulate the adoption of the technology leading to reductions in on-farm methane emissions.
Keywords: Choice experiment; mixed logit; adoption; biodigester defects